Pulmonary TB Prevention Through Information and Education to the Community - Syaharuddin Syaharuddin; Zusana A. Sasarari; Gustini Gustini; Anita Lontaan (Edukasi Ilmiah Indonesia, 2025)
Pulmonary tuberculosis (TB) is an infectious infectious disease that is a public health challenge in Indonesia. The disease is caused by Mycobacterium tuberculosis and has a high rate of transmission, especially in environments with low health awareness. Increasing public knowledge and understanding of the prevention of pulmonary TB is a very important preventive step in reducing the transmission rate. The Community Service Program (PkM) aims to provide information and education to the public about pulmonary TB, including its causes, symptoms, ways of transmission, and prevention efforts. This activity is carried out with a participatory approach through counseling, group discussions, and distribution of health information materials. The main target is vulnerable groups in certain areas that have a high prevalence of pulmonary TB. The implementation method includes three main stages: (1) preparation in the form of identification of needs and development of educational modules, (2) implementation in the form of implementation of counseling sessions and interactive discussions, and (3) evaluation in the form of community knowledge surveys before and after activities. The data was analyzed descriptively to measure changes in the level of public understanding. The results showed a significant increase in public understanding of pulmonary TB, especially related to prevention through a healthy lifestyle, good home ventilation, and the importance of early treatment. The evaluation also revealed the community's commitment to implement the preventive measures that have been conveyed in the activity. In conclusion, information and education through PkM are effective in increasing public awareness and knowledge about the prevention of pulmonary TB. It is hoped that similar activities can continue to be carried out on a sustainable basis to support the national program to eradicate pulmonary TB in Indonesia.